The association between combined oral contraceptive use and overweight/obesity: a secondary data analysis of the 2016 Ethiopia Demographic and Health Survey. Issue 12 (24th December 2020) - Endalifer, Melese Linger; Diress, Gedefaw; Addisu, Amanuel; Linger, Bedilu
Abstract : Objectives: In this study, we aimed to assess the association between combined oral contraceptive (OC) use and overweight/obesity among Ethiopian adult women of reproductive age. Design, setting and participants: The data were extracted from the 2016 Ethiopia Demographic and Health Survey; these data were collected from nine regions and two city administrations. We analysed the data from a total of 11 018 women aged 18–49 years who met eligibility criteria. Main outcome measures: We employed WHO criteria to classify the body mass index of women. Specifically we tested the association between combined OC utilisation with overweight/obesity after controlling for confounding variables. Result: The prevalence of combined OC utilisation was 1.7% and the prevalence of overweight/obesity was 8.6% among adult women of reproductive age. Use of combined OC increases the odds of overweight/obesity by two times among adult women of reproductive age after controlling for potential confounders (adjusted OR=1.902 (1.064–3.399)). Conclusion: In conclusion there is significant association between combined OC use and overweight/obesity. The findings have important implications for policymakers to design evidence based policy approachs to obesity prevention for women and at large for government to recognise the negative consequences of combined OC on women health.